Rheological properties study of high-viscosity asphalt based on direct coal liquefaction residue - Yong, Liu; Yong, Wang; Yanyan, Ru; Yandan, Li; Yongxiang, Li; Zhong, Gao (Frontiers in Built Environment, 2025)
Direct coal liquefaction residue (DCLR), a byproduct of the coal-to-oil process, poses a significant challenge for resource recycling and high-value utilization. Research has found that DCLR performs well in high temperature performance, but its shortcomings in low temperature performance remain a key issue limiting its widespread application. This research employs a composite modification approach, using DCLR as the primary material and incorporating SBS, rubber powder, aromatics oil, plasticizers, and stabilizers to prepare DCLR high-viscosity modified bitumen. The optimal formula was determined as 6% Styrene-Butadiene Styrene block copolymer (SBS) + 5% DCLR + 3% Dibutyl phthalate (DBP) + 10% rubber powder + 4% aromatics oil + 0.15% stabilizer. Performance tests showed that the rutting factor of the DCLR high-viscosity asphalt was 59.8% higher than that of the LT high-viscosity asphalt, and the G*/sinδ value after Rolling Thin Film Oven Test (RTFOT) aging had the smallest increase, confirming its excellent high-temperature rut resistance and resistance to short-term aging. The zero-shear viscosity (ZSV) values obtained by fitting the Carreau model indicated that within the temperature range of 46°C–64°C, the ZSV values of the DCLR modified asphalt were 1-2 orders of magnitude higher than those of the control samples, and the asphalt still maintained stable viscoelasticity at high temperatures (64°C), demonstrating its outstanding interfacial bonding performance. The bending beam rheometer (BBR) test results showed that the creep stiffness modulus of the three asphalts decreased while the creep rate increased, and the creep stiffness and creep rate had an approximate exponential relationship with temperature. Under the same temperature conditions, the stiffness modulus and creep rate of the DCLR high-viscosity asphalt were not significantly different from those of the Lutai (LT) high-viscosity asphalt, indicating its relatively good low-temperature crack resistance. Fluorescence microscopy results revealed that the DCLR system formed a stable three dimensional colloidal skeleton structure between the modifier molecules and the asphaltenes, which is the fundamental reason for its superior performance and low-temperature properties compared to the LT high-viscosity asphalt.